Association of prehospital hypotension depth and dose with survival following out-of-hospital cardiac arrest. (November 2022) - Smida, Tanner; Menegazzi, James J.; Crowe, Remle P.; Weiss, Leonard S.; Salcido, David D.
Abstract: Introduction: Hypotension following resuscitation from out-of-hospital cardiac arrest (OHCA) may cause harm by exacerbating secondary brain injury; however, limited research has explored this relationship. Our objective was to examine the association between duration and depth of prehospital post return of spontaneous circulation (ROSC) hypotension and survival. Methods: We utilized the 2019 and 2020 ESO Data Collaborative public use research data sets for this study (ESO, Austin, TX). Hypotension dose (mmHg*min.), average prehospital systolic blood pressure (SBP), and lowest recorded prehospital SBP were calculated. The association of these measures with survival to home (STH) and rearrest were explored using multivariable logistic regression. Time to hypotension resolution analyses by hypotension management strategy (push dose vasopressors, vasopressor infusion, or fluid only) were conducted using adjusted Cox proportional hazards models. Results: 17, 280 OHCA patients met inclusion criteria, of which 3, 345 had associated hospital outcome data. Over one-third (37.8%; 6, 526/17, 280) of all patients had at least one recorded SBP below 90 mmHg. When modeled continuously, average prehospital SBP (1.19 [1.15, 1.23] per 10 mmHg), lowest prehospital SBP (1.20 [1.17, 1.24] per 10 mmHg), and hypotension dose (0.995 [0.993, 0.996] per mmHg*min.) were independently associated with STH. Differences in hypotension management were not associated with differences in survival or time to hypotension resolution. Conclusion: Severity and duration of hypotension were significantly associated with worse outcomes in this dataset. Defining a threshold for hypotension requiring treatment above the classical SBP threshold of 90 mmHg may be warranted in the setting of prehospital post-resuscitation care.